Play beyond the screen : nurturing a healthier child with lesser screen time - Woo, Annabelle Xue Qi (Nanyang Technological University, 2020)
Today’s digital landscape has led to a significant increase in screen time usage amongst young children. The Growing Up in Singapore Towards Healthy Outcomes (GUSTO) study found 3 in 4 Singaporean children aged 2 exceed the American Academy of Paediatric’s recommended screen time guidelines. Yet, there is a lack of local literature and campaigns advocating for a regulation of screen time. This paper presents ​Play Beyond The Screen, a pioneering health communications campaign aimed to encourage parents with children aged 1-5 to actively mediate their children’s screen time usage and employ alternative measures to educate and entertain them. Additionally, the campaign sought to bridge the knowledge gap between the negative health impacts of excessive screen time and delayed childhood development. Guided by the campaign’s strategic pillar to foster a culture of sharing, ​Play Beyond The Screen ​provided parents with sensory play ideas and craft activities to inspire parents to experiment with other simple screen-free alternatives. This served as conversation starters to spark off further discussion surrounding offline interactive play amongst parenting communities. The campaign’s success is most evident through high numbers of organic user-generated content that resulted from the ​Panel Sharing cum Children’s Workshop ​and ​Stay-Home Play Kit ​tactics. Overall, ​Play Beyond The Screen ​cast a renewed spotlight on the issue of excessive screen time and instilled confidence in parents to kickstart screen-free management behaviours. As children continue to be exposed to technology at younger ages, there is room for expansion of the campaign on a national scale to ensure its sustainability.